1989
DOI: 10.1111/j.1423-0410.1989.tb00823.x
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Eliminate HLA Class I Antigens from Platelet Surface without Cell Damage: Acid Treatment at pH 3.0

Abstract: A new method was studied for eliminating HLA class I antigens from the surface of platelets without damaging the cells. Platelets were exposed to an acid solution (pH 3.0) to eliminate the antigenicity of HLA class I antigens. The reduction in antigenicities of HLA class I common antigen and individual HLA class I antigens by acid treatment was marked. Patients' sera which contained multispecific HLA antibodies reacted with PBS-treated platelets, but not with acid-treated platelets. No changes were observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…This method was developed by Kurata et a1. 42 and was similar to that successfully applied in one case by Shanwell et a1. platelet-rich plasma and buffy coat methods4 In our studies, we replaced the plasma employed by Shanwell et al with Plasmalyte-A (Baxter, Deerfield, IL), a crystalloid solution used as a replacement fluid in surgery, which proved to be a suitable platelet storage medium.…”
Section: Where Lemons Could Helpsupporting
confidence: 63%
“…This method was developed by Kurata et a1. 42 and was similar to that successfully applied in one case by Shanwell et a1. platelet-rich plasma and buffy coat methods4 In our studies, we replaced the plasma employed by Shanwell et al with Plasmalyte-A (Baxter, Deerfield, IL), a crystalloid solution used as a replacement fluid in surgery, which proved to be a suitable platelet storage medium.…”
Section: Where Lemons Could Helpsupporting
confidence: 63%
“…Alloantiserum having antibody speci ficity to HLA A24 and B51 was obtained from a patient with chronic renal failure [14],…”
Section: Antiseramentioning
confidence: 99%
“…Immunofluorescence flow cytometry (FCM) was performed as pre viously described [14], Briefly, fresh platelets were treated with acid, chloroquine or PBS as described above, washed once, and then fixed with paraformaldehyde. After washing three times, the platelets were incubated with test sera for 45 mm at 37°C.…”
Section: Immunofluorescence Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…From their observations that incubation of platelets in acid hypertonic solutions of chloroquine removes HLA-A and HLA-B antigenic material from platelets but not from lymphocytes, Blumberg et al [1] concluded that HLA class I antigens on platelets are adsorbed from plasma rather than that they are integral platelet membrane proteins. HLA antigenicity can also be eluted in acid buffers at pH 3 [2]. 'Elution of HLA antigens' has been explained by Neumüller et al [3] as loss of conformational integrity of the HLA molecule following dissociation of β2-microglobulin and the HLA heavy chain.…”
Section: Immunogenic Structures Of the Platelet Membranementioning
confidence: 99%